Stapled orthotopic ileal neobladder after radical cystectomy for bladder cancer: Functional results and complications over a 20-year period. Issue 3 (March 2016) - Muto, G.; Collura, D.; Simone, G.; Muto, G.L.; Rosso, R.; Giacobbe, A.; Castelli, E.
Abstract: Aims: To present the long term-results and complications of a large series of stapled ileal orthotopic neobladders. Materials and methods: From 1992 to 2012 we performed 606 radical cystectomies with stapled orthotopic neobladder substitution in male patients. The median patient age was 65 years (interquartile range [IQR]: 58–71). Results: Median operative time was 205 min (IQR: 180–225). The overall survival rates at 5, 10, 15, and 20 yr were 68% (336 of 494), 55% (207 of 376), 38% (98 of 259), and 23% (14 of 62), respectively, and the disease specific survival rates were 75% (371 of 494), 59% (222 of 376), 50% (130 of 259), and 35% (22 of 62), respectively. After a median follow-up of 81 months (IQR: 30–144), a total of 147 early (less than 90 days) complications (38 diversion related, 109 diversion unrelated) occurred in 144 patients (24%); 163 late complications (141 diversion related, 22 diversion unrelated) affected 141 patients (23%). At 60 months, daytime and nighttime continence was complete in 96% and 72% of cases, respectively. Urodynamic studies showed that maximum capacity, residual volume, maximum flow rate, pressure at maximum capacity, and maximum outlet closure pressure were not statistically different at 12 and 60 months postoperatively. Conclusions: The use of a stapler when performing orthotopic neobladders significantly reduces the operating time, and offers good functional results with acceptable complication rates. Our results could encourage the use of a stapler when performing an ileal neobladder during laparoscopic and robotic radical cystectomies.